2013 IEEE 14th International Symposium on "A World of Wireless, Mobile and Multimedia Networks" (WoWMoM) 2013
DOI: 10.1109/wowmom.2013.6583440
|View full text |Cite
|
Sign up to set email alerts
|

Applying delay tolerant networking routing algorithms in maritime communications

Abstract: The availability of off-the-shelf equipment that facilitates long range wireless connectivity can prove to be useful in maritime communications. By establishing terrestrial wireless links, vessels may exchange data between them or with shore-based stations avoiding the use of costly satellite connectivity. On the other hand, vessel mobility and large distances between its nodes make a wireless maritime network hard to manage; frequent disconnections are expected to be the norm in this primarily low node densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The results showed that, in some scenarios, a boat chain can be established for transporting information from a far node to the gateway on land in a multi-hop fashion, but, in other cases, some boats are isolated with no communication capabilities. In order to solve the issue of temporally isolated nodes due to frequent disconnections, the use of Delay Tolerant Networks (DTN) have been proposed as well [20,21]. Work in [20] explored the use of WiMAX-based technology for over the horizon ship-to-ship communications following a DTN scheme.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that, in some scenarios, a boat chain can be established for transporting information from a far node to the gateway on land in a multi-hop fashion, but, in other cases, some boats are isolated with no communication capabilities. In order to solve the issue of temporally isolated nodes due to frequent disconnections, the use of Delay Tolerant Networks (DTN) have been proposed as well [20,21]. Work in [20] explored the use of WiMAX-based technology for over the horizon ship-to-ship communications following a DTN scheme.…”
Section: Related Workmentioning
confidence: 99%
“…The results, attained by means of computing simulation, showed superior performance of DTN-oriented routing protocols in comparison with traditional MANET routing algorithms. In turn, the authors of [21] also made use of simulation tools to demonstrate that DTN are a viable option, but, even more important, that as vessel mobility patterns can be well-known beforehand, the upcoming network topology changes can be accurately predicted. Considering this fact, more efficient routing algorithms can be developed within the context of DTN.…”
Section: Related Workmentioning
confidence: 99%
“…Alternatively, Mobile Ad-hoc Networks (MANETs) have a more distributed network architecture where routing protocols do not necessarily require nodes with particular roles [122]. MANETs have already been proposed for maritime environments [109,123], but the characteristics, constraints and challenges of such environments require additional considerations such as Disruptive or Delay Tolerant Networking (DTN) and different routing protocols [113,114,116]. Table 3 presents networking options used in the literature, regarding common communication technologies, and which may be applied to various types of autonomous vehicles.…”
Section: Network and Protocolsmentioning
confidence: 99%
“…The DTNs architecture has also been simulated to send messages to a remote village by buses, boats, and other public transports [33] and communications ship-to-ship in the maritime environment networks [34]. In [33], the model of public transport motion is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The sizes of messages used are 25, 50, 75, and 100 MBytes, but the number of messages each message size is unknown. Instead, the actual vessel movement data is used in [34]. The simulation was performed with transmit range 1-50 Km, infinite buffer size and time to live, and size of 10 MByte message.…”
Section: Introductionmentioning
confidence: 99%